EFEKTIVITAS JALUR SEPEDA MOTOR PADA JALAN PERKOTAAN MENGGUNAKAN MODEL SIMULASI-MIKRO - Zukhruf, Febri; Bona Frazila, Russ; Wibowo, Sony S . (Jurnal Transportasi, 2010)
The Growth of motorcycles in Indonesia creates high proportion of motorcycles on traffic flow. This high proportion, which is very dominant, creates some traffic problems, including traffic jam dan traffic accidents. There are several methods available to solve the problems; for example providing motorcycle lane and slow lane for the movement of motorcycles. The purpose of this study is to determine the effectiveness of motorcycle lane and slow lane using microsimulation model. The results show that the microsimulation model can only be used for road sections with the average motor cycle speed less than 40 km per hour.Keywords: high proportion of motorcycle, microsimulation, motorcycle lane, slow lane